The Use of Picture Prompts to Improve Students’ Writing in Descriptive Texts - Ratnawati (Journal of Innovative and Creativity, 2022)
This final project is about the use of picture prompts to improve students‘ writing in descriptive texts at the eighth grade students of SMP N 5 Tambusai Utara, Rokan Hulu in the academic year of 2021. An action research was conducted to find out in what ways picture prompts could improve students‘ writing in descriptive texts. The subject of this research was 31 students of eighth grade students since they got problem in mastering descriptive texts. I used some writing tests, field notes, and questionnaires in collecting the data. In this research I conducted two cycles consisted of cycle one and cycle 2. In cycle one, there were a pre test, three meetings for treatment, and a formative test. In cycle two, there were three meetings for treatment and a post test. The result of the data showed a significant improvement of the students‘ writing. The students‘ writing improved in all writing aspects including grammar, vocabulary, mechanic and relevance. The average results after conducting the research improved; pre test (57.58), formative test (65.00), and post test (81.13). Furthermore, based on questionnaires and field notes, it shows that the implementation of picture prompts made the students‘ behavior changed. They were more interested in writing descriptive texts. The prompts could ease their problem and helped them in revealing the ideas. Therefore, it can be concluded that picture prompts as learning media contributes to the improvement of students‘ writing in descriptive texts.